Multifarious diagnostic possibilities of the S100 protein family: predominantly in pediatrics and neonatology - Medkova, Anna; Srovnal, Josef; Potomkova, Jarmila; Volejnikova, Jana; Mihal, Vladimir (World journal of pediatrics, 2018)
BACKGROUND: Numerous articles related to S100 proteins have been recently published. This review aims to introduce this large protein family and its importance in the diagnostics of many pathological conditions in children and adults. DATA SOURCES: Based on original publications found in database systems, we summarize the current knowledge about the S100 protein group and highlight the most important proteins with focus on pediatric use. RESULTS: The S100 family is composed of Ca2+ and Zn2+ binding proteins, which are present only in vertebrates. Some of these proteins can be used as diagnostic markers in cardiology (S100A1, S100A12), oncology (S100A2, S100A5, S100A6, S100A14, S100A16, S100P, S100B), neurology (S100B), rheumatology (S100A8/A9, S100A4, S100A6, and S100A12), nephrology and infections (S100A8, S100A9, S100A8/A9, S100A12). The most useful S100 proteins in pediatrics are S100A8, S100A9, heterodimers S100A8/A9, S100B and S100A12. CONCLUSIONS: The S100 family members are promising biomarkers and provide numerous possibilities for implementation into clinical practice to optimize the differential diagnostic process.
Keywords: dospělí; Neonatology; Female; Infant; dítě; biologické markery; pediatrie; novorozenec; Biomarkers; Adult; ženské pohlaví; Predictive Value of Tests; prediktivní hodnota testů; S100 Proteins; lidé; Infant, Newborn; Sensitivity and Specificity; senzitivita a specificita; prognóza; Diagnostics; Male; kojenec; Marker; Prognosis; neonatologie; proteiny S100; Child; S100; Pediatrics; mužské pohlaví; Humans